Development of sorghum hybrids for stable yield and resistance to grain mold for the Center and South-East of Senegal. (May 2019) - Diatta, Cyril; Tovignan, Thierry Klanvi; Adoukonou-Sagbadja, Hubert; Aidara, Ousmane; Diao, Yagouba; Sarr, Mame Penda; Ifie, Beatrice Elohor; Offei, Samuel Kwame; Danquah, Eric Yirenkyi; Cisse, Ndiaga
Abstract: Panicle mold infestation is reported to cause 30–100% yield loss in sorghum. Therefore, breeding for mold resistance becomes a necessity. Due to difficulties in predicting genotype by environment interactions (GxE), multi-location tests are required in the breeding process to identify high-yielding and stable genotypes across environments. The present study aimed at assessing the performance and stability for yield and resistance to grain mold of five local sorghum hybrids evaluated over five years across four locations in the Center and South-East regions of Senegal. The combined ANOVA showed a strong effect of year, genotype and location on the days to anthesis, plant height, grain yield components and panicle grain mold rating score. The GxE interaction was significant for grain yield but not for panicle mold infestation. Year x location explained 25% of total variation of grain yield while year and location explained 22% and 19% respectively. With regard to panicle grain mold infestation, year explained 32% of total variation followed by year by location (29%), genotype (7%) and location (6%). Although year and location better explained the variation for the traits, broad-sense heritability was high, indicating a possibility to improve these traits through selection. For most of the traits, the hybrids had higher performance compared to the parental lines used as check, showing an expression of heterosis. The GGE biplot approach was used to identity hybrids with high performance and stability. Hence, hybrid G4 followed by G2 and G3, were the best in terms of yield performance and stability. Moreover, location STM15 followed by DAR15 were the best closest to an ideal location. Overall, G5 was pointed out as the best hybrid combining grain yield and mold tolerance across years and locations. These results in addition to providing details on the performance and stability of the five sorghum hybrids helped to identify the best hybrids to be released and disseminated in the Center and South-East regions of Senegal. Highlights: Five sorghum hybrids with their parents were screened for yield performance and stability and resistance to grain mold. GxE interaction was significant for grain yield but not for panicle mold infestation. Hybrids expressed higher performance compared to the parental lines. GGE-biplot was efficiently used to identify the best and stable hybrids. Some hybrids combined both grain yield and resistance to grain mold.